2015
DOI: 10.1111/mec.13062
|View full text |Cite
|
Sign up to set email alerts
|

Limited influence of local and landscape factors on finescale gene flow in two pond‐breeding amphibians

Abstract: Dispersal and gene flow within animal populations are influenced by the composition and configuration of the landscape. In this study, we evaluated hypotheses about the impact of natural and anthropogenic factors on genetic differentiation in two amphibian species, the spotted salamander (Ambystoma maculatum) and the wood frog (Lithobates sylvaticus) in a commercial forest in central Maine. We conducted this analysis at two scales: a local level, focused on factors measured at each breeding pond, and a landsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 138 publications
2
41
0
Order By: Relevance
“…At spatial scales similar to those in this study, Ambystoma salamanders display high levels of gene flow between populations (Newman & Squire ; Zamudio & Wieczorek ; Purrenhage, Niewiarowski & Moore ; Coster et al . ). However, this connectivity is spatially dependent, with greater population differentiation at larger scales, as would be predicted by an isolation‐by‐distance model.…”
Section: Discussionmentioning
confidence: 97%
“…At spatial scales similar to those in this study, Ambystoma salamanders display high levels of gene flow between populations (Newman & Squire ; Zamudio & Wieczorek ; Purrenhage, Niewiarowski & Moore ; Coster et al . ). However, this connectivity is spatially dependent, with greater population differentiation at larger scales, as would be predicted by an isolation‐by‐distance model.…”
Section: Discussionmentioning
confidence: 97%
“…Leaving aside the common effect of topography on both species, land cover‐related categorical variables did not have an important role in shaping genetic structure. Some studies have previously reported negative effects of roads on gene flow in anurans (Richardson, ) and salamanders (Coster et al., ). Nevertheless, models including road density as a variable were not well supported in either species (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative landscape genetics studies on codistributed species have great potential to design cost‐effective conservation plans focusing on measures favouring a wider set of taxa, but are still relatively scarce. So far, comparative studies have focused primarily on vertebrates, including amphibians (Coster, Babbitt, Cooper, & Kovach, ; Richardson, ; Zancolli, Rödel, Steffan‐Dewenter, & Storfer, ), mammals (Dudaniec et al., ; Frantz et al., ; Muscarella, Murray, Ortt, Russell, & Fleming, ), and fishes (Olsen et al., ) and more occasionally on invertebrates (Engler, Balkenhol, Filz, Habel, & Rödder, ; Ortego, García‐Navas, Noguerales, & Cordero, ; Phillipsen et al., ). These multi‐species studies may allow identifying interspecific differences in the way landscape features influence connectivity and gene flow and provide general guidelines for land management programmes aimed at protecting biological communities or ecosystems (Goldberg & Waits, ; Keller, Holderegger, Strien, & Bolliger, ; Nicholson & Possingham, ; Schwenk & Donovan, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracking studies suggest altered habitats between pools can reduce overall dispersal propensities (Cline & Hunter, , ). Despite these observed ecological effects, signals of urbanization‐related influences on the genetic structure of pool‐breeding amphibians have not been consistently detected (e.g., Coster, Babbitt, Cooper, & Kovach, ; Peterman et al, ; Richardson, ; Table ). In some of these cases, a lack of effect could be associated with the surveyed spatial extents that were relatively small and that may not be commensurate with the scales over which drift–migration equilibrium is most disrupted and detectable.…”
Section: Introductionmentioning
confidence: 99%